A Novel Self-Assessment Method for Training Access Cavity on 3D Printed Endodontic Models - Matteo Meglioli; Giovanni Mergoni; Francesco Artioli; Benedetta Ghezzi; Maddalena Manfredi; Guido Maria Macaluso; Simone Lumetti (MDPI AG, 2023)
Background: New technologies can facilitate the transition from pre-clinical to clinical settings. We investigate students' satisfaction with a novel learning method adopted in access cavity exercises. Methods: Students performed their access cavity on inexpensive, in-house 3D printed teeth. Their performances were evaluated by scanning the prepared teeth with an intraoral scanner and visualized using a mesh processing software. Then, the same software was used to align the tooth prepared by the student and the teacher's one for self-assessment purposes. Students were asked to answer a questionnaire about their experiences with this new learning method. Results: From the teacher's perspective, this novel learning approach was easy, straightforward and affordable. Overall, student feedback was positive: 73% found that access cavity assessment by scanning was more useful compared to a visual inspection under magnification and 57% reported that they had a better understanding of errors and mishaps. On the other hand, students pointed out that the material used to print teeth was too soft. Conclusion: The use of in-house 3D printed teeth in pre-clinical training is a simple way to overcome some of the drawbacks associated with extracted teeth, such as limited availability, variability, cross-infection control, and ethical constraints. The use of intraoral scanners and mesh processing software could improve student self-assessment.